Hbr1 Activates and Represses Hyphal Growth in Candida albicans and Regulates Fungal Morphogenesis under Embedded Conditions - Pendrak, Michael L. (PLoS One, 2015)
Transitions between yeast and hyphae are essential for Candida albicans pathogenesis. The genetic programs that regulate its hyphal development can be distinguished by embedded versus aerobic surface agar invasion. Hbr1, a regulator of white-opaque switching, is also a positive and negative regulator of hyphal invasion. During embedded growth at 24°C, an HBR1/hbr1 strain formed constitutively filamentous colonies throughout the matrix, resembling EFG1 null colonies, and a subset of long unbranched hyphal aggregates enclosed in a spindle-shaped capsule. Inhibition of adenylate cyclase with farnesol perturbed the filamentation of HBR1/hbr1 cells producing cytokinesis-defective hyphae whereas farnesol treated EFG1 null cells produced abundant opaque-like cells. Point mutations in the Hbr1 ATP-binding domain caused distinct filamentation phenotypes including uniform radial hyphae, hyphal sprouts, and massive yeast cell production. Conversely, aerobic surface colonies of the HBR1 heterozygote on Spider and GlcNAc media lacked filamentation that could be rescued by growth under low (5%) O(2). Consistent with these morphogenesis defects, the HBR1 heterozygote exhibited attenuated virulence in a mouse candidemia model. These data define Hbr1 as an ATP-dependent positive and negative regulator of hyphal development that is sensitive to hypoxia.